PENDIDIKAN JASMANI DI SEKOLAH MENENGAH ATAS: ANTARA HARAPAN DAN KENYATAAN - Nurhadi Santoso (Jurnal Pendidikan Jasmani Indonesia, 2009)
Physical education in secondary school is considerably essential for paving the way for the realization of the national education objectives in regard to the nurturing efforts for better characters of the people of Indinesia. Through a well organized physical education instruction by implementing environment management, the learning process is expected to go along with the objectives of the basic competence. In so doing, physical education essentials such as the physical well-being of children, as well as their intellectual, an varied skills development they need for their future life are achievable. Environment management that a teacher can do in order to make the instructional process proceed well covers the student, time, room, equipment, fasilities management and distribution as well as tools procurement. With this concept in mind, the assurance of quality physical education learning process is well maintaned. Thus, environment management to physical education becames part of the physical education teachers main job that should be done properly in addition to the management of teaching task, teaching materal delivery, and instructional atmosphere. Keywords: Management, Learning Experience, Movement Task, Physical Education